Adapting SDN datacenters to support cloud IIoT applications - Gonçalves, Pedro (2015)
IIoT (Industrial Internet of Things) cloud applications require reliable, fault-tolerant networks, supporting real-time guarantees and allowing interaction with other applications already existing in the datacenter. The Software Defined Networks (SDN) paradigm is especially suited for the management of the network cloud because of its fine grained admission control and the management flexibility provided by the centralized resource management. This paper presents a SDN management approach for IIoT datacenters, which provides an efficient fault-tolerant network, enabled with deterministic QoS guarantees. By taking advantage of a centralized resource management mechanism, the proposed solution integrates topology definition with resource allocation, allowing to efficiently distribute available network resources for admitted packet flows.